LZAP is a novel Wip1 binding partner and positive regulator of its phosphatase activity in vitro - Wamsley, J. Jacob (Cell Cycle, 2016)
The phosphatase Wip1 attenuates the DNA damage response (DDR) by removing phosphorylation marks from a number of DDR proteins (p53, MDM2, Chk1/2, p38). Wip1 also dephosphorylates and inactivates RelA. Notably, LZAP, a putative tumor suppressor, has been linked to dephosphorylation of several of these substrates, including RelA, p38, Chk1, and Chk2. LZAP has no known catalytic activity or functional motifs, suggesting that it exerts its effects through interaction with other proteins. Here we show that LZAP binds Wip1 and stimulates its phosphatase activity. LZAP had been previously shown to bind many Wip1 substrates (RelA, p38, Chk1/2), and our results show that LZAP also binds the previously identified Wip1 substrate, MDM2. This work identifies 2 novel Wip1 substrates, ERK1 and HuR, and demonstrates that HuR is a binding partner of LZAP. Pleasingly, LZAP potentiated Wip1 catalytic activity toward each substrate tested, regardless of whether full-length substrates or phosphopeptides were utilized. Since this effect was observed on ERK1, which does not bind LZAP, as well as for each of 7 peptides tested, we hypothesize that LZAP binding to the substrate is not required for this effect and that LZAP directly binds Wip1 to augment its phosphatase activity.